2023
DOI: 10.1001/jamanetworkopen.2022.50996
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rates of Completion, Delays, and Participant Recruitment in Randomized Clinical Trials in Surgery

Abstract: ImportanceDiscontinuation and nonpublication are established sources of avoidable waste among surgical trials, but rates of delayed completion and recruiting shortfalls remain unclear.ObjectivesTo examine the rate of delayed completion, incomplete enrollment, and discontinuation among randomized clinical trials in surgical populations and the duration of delays and extent of recruiting shortfalls among these trials.Design, Setting, and ParticipantsThis cross-sectional study examined randomized clinical trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 10 , 19 , 20 Another study that grouped surgical RCTs as a whole found a completion rate of 78.5% of the 2542 included trials, which is a stark contrast to our finding and further highlights the scope of the problem. 9 A majority of the trials we examined were open-label and single-center, falling short of the true gold standard of a blinded multicenter RCT, further supporting the need to improve on current processes.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 10 , 19 , 20 Another study that grouped surgical RCTs as a whole found a completion rate of 78.5% of the 2542 included trials, which is a stark contrast to our finding and further highlights the scope of the problem. 9 A majority of the trials we examined were open-label and single-center, falling short of the true gold standard of a blinded multicenter RCT, further supporting the need to improve on current processes.…”
Section: Discussionmentioning
confidence: 95%
“…Within the group of “unknown” status studies, the median time from trial initiation to date of data extraction in April 2023 was 7.7 years, which suggests that these 17 studies have likely been abandoned or discontinued as a prior study using the ClinicalTrials.gov database demonstrated that the median time to study discontinuation is 2.2 years. 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An estimated 47% of CTs are completed, 27% are in various recruitment stages, 11% have been discontinued, and 15% have unknown statuses. Given CT discontinuation rates of 8.5%-22.7% in medicine 24,25 and 21.5% in surgery, 26 the 11% rate in PRS CTs indicates a comparatively higher completion rate. Half (50.8%) of CT phases are labeled "not applicable" due to nonconventional structures.…”
Section: Characteristics Of Global Prs Trialomementioning
confidence: 99%
“…However, conducting a successful clinical trial can be challenging [ 2 ]. A key contributor to clinical trial failure is low participant recruitment rates [ 3 , 4 ]; up to 35% of clinical trials are discontinued because of difficulties recruiting participants [ 5 ] and only 17% of randomised clinical trials in surgery reach target sample sizes within the planned timeframe [ 4 ]. Additionally, one third of completed clinical trials are at risk of being underpowered as pre-specified recruitment targets are not attained, jeopardising the trustworthiness of trial findings [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%